Analisis Dampak Program Bank Sampah Bagi Masyarakat Urban: Studi Kasus Di Kota Makassar - Dita Angraeni Sutiawati; Muhammad Abdullah; Andi Ahmad Yani (Development Policy and Management Review (DPMR), 2021)
Based Law No. 18 of 2008 on waste management, the Government makes litter bank program to address the issue of solid waste to be one of the main problems with implementing the waste management system 3R (reduce, reuse, recycle). In Makassar there are various programs that deal with issues of cleanliness, one waste bank program assist the government in reducing waste reduction and able to empower people to care about the cleanliness. The purpose of this research is to describe the impact of the waste bank program for the community in the bakung village. The research approach used is a descriptive qualitative approach. Data collection techniques using interviews, observation and documentation while the source of the data used comes from primary data and secondary data.The results of this research indicate that the presence of the waste bank program had a positive impact for the community in the economic, social and environmental. In the economic aspect can increase people's income, while the social aspects of increased social interaction, knowledge about waste management and manufacturing of handicraft. In the environmental aspect, people feel secure with their surroundings and be able to sort the waste according to type. Keywords: Impact Program; Waste Bank Program; Waste Management and Society.